Development of Smart Beater and Pole Base Kasti Ball Game for Elementary School - Karsam Karsam; Ade Rahmat; Muhammad Suhairi (Inspiree)
The  purpose  of  the study. Development of batting equipment adapted to the developmental characteristics of children in elementary schools and portable baseball perch poles, which can be used on dirt and concrete courts.